Effect on structure, stability, and H+ irradiation on Nd3+/Ru4+‐loaded iron phosphate glass for nuclear applications. Issue 4 (13th December 2022) - Joshi, Akhilesh C.; Roy, Mainak; Dutta, Dimple P.; Mishra, Raman K.; Meena, Sher Singh; Kumar, Ravi; Tyagi, Avesh K.
Abstract: Nuclear energy generation technology is critically linked with the safe disposal of radioactive waste. In this context, iron phosphate glass (IPG) is gaining predominance as nuclear waste vitrification matrix that necessitates a thorough study on the effect of the loading of various nuclear fission waste materials in it. In this study, the effect of the loading of Nd 3+ (which acts as a surrogate for radioactive curium (Cm)) and Ru 4+ (which is a fission product of 235 U) in IPG has been assessed. The optimum loading of Nd 3+ /Ru 4+ leading to the formation of homogenous melt has been ascertained via powder X‐ray diffraction and scanning electron microscopy techniques. The modification in the Fe 3+ /Fe 2+ ratio in IPG and the consequent change in its average coordination number with Nd 3+ /Ru 4+ loading has been deduced from the Mössbauer studies. Local structure analysis has been done using X‐ray absorption spectroscopy at Nd/Ru/Fe K ‐edge (as applicable) for all the single and co‐loaded IPG samples. All the co‐loaded samples show enhanced glass stability and glass forming ability compared to unloaded IPG which has been ascertained via detailed thermal studies. The variation in IPG network structure on the addition of Nd2 O3 and RuO2 has been ascertained through spectroscopic techniques like Fourier transform infrared (FTIR) and Raman. The base glass and a few representative homogenous single and co‐loaded IPG samples have been irradiated with 4.5 MeV proton beam to simulate the hosting of radioactive elements and the radiation effect on glass structure has been ascertained using FTIR and Raman spectroscopies. The suitability of IPG as nuclear waste vitrification matrix for Nd 3+ and Ru 4+ is established through all the above analyses. Abstract :